Violating Human Rights? : Substance of Human Rights in Disparity as a Result of Determination of Interfaith Marriage Application in District Court - AD, Muhammad Irfan; Falah, Mohammad Bachrul; Mahatta, Afdhalia; Ikhwan, Muhammad (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2023)
This study aims to explore the substance of human rights in two stipulations of the application for registration of interfaith marriages in the District Court. Stipulation Number 916/Pdt.P/2022/PN. Sby granted the application, while Stipulation Number 71/Pdt.P/2017/PN. Bla did not grant it. The type of research used is normative legal research with a case approach and comparative approach. The result of Stipulation Number 916/Pdt.P/2022/PN. Sby accommodates human rights with the implementation of natural rights that are part of the universality of human rights, on the grounds of the right to freedom of religion and family. The Stipulation Number 71/Pdt.P/2017/PN. Bla contains the substance of human rights in the realm of cultural relativity, through factual considerations from the interpretation of judges and religious leaders regarding the prohibition of interfaith marriages. Therefore, although outwardly the two are contradictory, they actually still accommodate the substance of human rights in their respective perspectives. This research contributes to opening up 'opportunities' for a broader interpretation of the fulfillment of human rights, by looking at the existence of human rights in the two stipulations above. Penelitian ini bertujuan untuk menggali substansi hak asasi manusia dalam dua hasil penetapan permohonan pencatatan perkawinan beda agama di Pengadilan Negeri. Penetapan Nomor 916/Pdt.P/2022/PN. Sby mengabulkan permohonan tersebut, sedangkan Penetapan Nomor 71/Pdt.P/2017/PN. Bla tidak mengabulkan. Jenis penelitian yang digunakan adalah penelitian hukum normatif dengan pendekatan kasus (case approach) dan perbandingan (comparative approach). Hasil Penetapan Nomor 916/Pdt.P/2022/PN. Sby mengakomodasi hak asasi manusia dengan implementasi hak kodrati yang menjadi bagian dari universalitas HAM, dengan alasan hak kebebasan beragama dan berkeluarga. Adapun Penetapan Nomor 71/Pdt.P/2017/PN. Bla mengandung substansi HAM dalam ranah relativitas budaya, melalui pertimbangan faktual dari interpretasi hakim dan tokoh agama mengenai pelarangan pernikahan beda agama. Oleh karena itu, meskipun secara zahir keduanya bertentangan, akan tetapi sejatinya tetap mengakomodasi substansi HAM dalam perspektif masing-masing. Penelitian ini berkontribusi untuk membuka ‘peluang’ interpretasi pemenuhan hak asasi manusia secara lebih luas, dengan melihat eksistensi hak asasi manusia dalam dua penetapan di atas.